Insecticidal activity of venomous saliva from Rhynocoris fuscipes (Reduviidae) against Spodoptera litura and Helicoverpa armigera by microinjection and oral administration - Sahayaraj,K (2011)
Rhynocoris fuscipes is a potential predator of many economically important pests in India. In the present study, its venomous saliva (VS) was collected by milking and diluted with HPLC grade water to different concentrations (200, 400, 600, 800 and 1000 ppm). Microinjection of Rhynocoris fuscipes VS was more toxic than its oral administration in Helicoverpa armigera (cotton bollworm) and Spodoptera litura (tobacco cutworm). Thus, R. fuscipes VS was found to be toxic to third instar S. litura and H. armigera with respective LD50s of 846.35 and 861.60 ppm/larva at 96 hours after microinjection. The current results showed that VS of Rhynocoris fuscipes caused mortality of H. armigera and S. litura. Active peptides from VS may be isolated, identified and assessed for their impact in order to ascertain how they alter the physiology of these pests, information that could be applicable in pest management programs.